Rancang Bangun Sistem Informasi Arsip Surat Berbasis Web dengan Menggunakan Framework CodeIgniter - Wihda Fitrotul Qolbi; Muhammad Taufiq; Taofik Muhammad (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
Letter archive management at MTs. Ar-Rahmah faces challenges in recording, storage, and document retrieval processes. This research developed a Web-Based Letter Archive Information System using PHP programming language, MySQL database, and CodeIgniter framework. The system addresses three critical archiving functions: document recording, storage, and efficient searching. Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) guided the development process. Software Engineering expert validation yielded a score of 70 out of 75, while user assessments from administrative staff and operators scored 150, and the principal's assessment reached 144. These scores classify the system as suitable for implementation, effectively resolving the previous archiving difficulties at MTs. Ar-Rahmah.